THE EFFICIENCY OF FINANCIAL SUPPORT FOR WATER INFRASTRUCTURE IMPROVEMENT IN BULGARIA - Stoyanova, Zornitsa Dimova (Economics of Agriculture, 2022)
Environmental challenges related to water resources lead to a change in water distribution. This will cause a change in water infrastructure which will need financial support. This article proposes an analysis of the efficiency of financial support for water infrastructure improvement in Bulgaria. The aim of the article is to describe state of the population’s access to water infrastructure and financial support for the development of the water infrastructure and based on the statistical data to analyze the eﬀectiveness of the financial support under OPE 2007-2013 and OPE 2014-2020, axis Water for the development of water infrastructure. The parts of the article are as follows: 1) Introduction, presenting the theoretical views on the financing for the improvement of the water infrastructure; 2) Research methodology 3) Analysis of the eﬀectiveness of financial support for the development of water infrastructure (correlation and DEA analysis); 4) General conclusions.